2021
DOI: 10.36877/pmmb.a0000236
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dietary Supplements Use among Healthcare Workers during the COVID-19 Pandemic in Malaysia

Abstract: Healthcare workers (HCWs) must be aware of the latest data supporting or refuting the use of oral dietary supplements (ODS) in order to disseminate evidence-based health information and help patients make informed decisions. Nevertheless, there is relatively scant data on the prevalence of dietary supplement use among HCWs, the types of dietary supplements recommended to patients by HCWs, and their reasons for recommending these products, particularly during the COVID-19 outbreak. This study examined the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…In vitro tests showed that the plant has a strong anti-inflammatory effect, inhibiting the degradation of bovine serum albumin (BSA) and chicken egg albumin (CEA), observed mainly in the stem extracts. Nuciferine (alkaloid) and fargesin (lignan) are among the main compounds identified in the stem extract according to chromatograms and MS/MS identification; they are phytochemical compounds known for their anti-inflammatory virtues [50,56] which proves the results of the antiinflammatory activities performed.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro tests showed that the plant has a strong anti-inflammatory effect, inhibiting the degradation of bovine serum albumin (BSA) and chicken egg albumin (CEA), observed mainly in the stem extracts. Nuciferine (alkaloid) and fargesin (lignan) are among the main compounds identified in the stem extract according to chromatograms and MS/MS identification; they are phytochemical compounds known for their anti-inflammatory virtues [50,56] which proves the results of the antiinflammatory activities performed.…”
Section: Discussionmentioning
confidence: 91%
“…Different studies conducted during the pandemic reported different results. Participants used multivitamins and Omega-3 in one study [33] while healthcare professionals in Malaysia used Vitamin C and multivitamins [34]. University students used multivitamins and vitamin C [35], and 21% of healthcare professionals in our country used vitamin D, 17% vitamin C and 9% vitamin B12 [30] as nutritional supplements [30,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, more rigorous clinical trials are required to determine the optimal dosage, safety, and efficacy of these remedies, especially those suffering from COVID-19 or long COVID [57][58][59] . Concurrently, efforts should be made to standardize herbal preparations to ensure consistent quality [60,61] .…”
Section: Herbal Drug Bioactivitiesmentioning
confidence: 99%